PENGARUH PENERAPAN TEACHING FACTORY, SELF-EFFICACY, DAN INTERNAL LOCUS OF CONTROL TERHADAP KESIAPAN KERJA SISWA BISNIS DIGITAL SMKN 1 JOMBANG - Nur Haslinda; Septyan Budy Cahya (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2026)
This study aims to determine the effect of the implementation of a teaching factory, self-efficacy, and internal locus of control on the work readiness of students majoring in Digital Business at SMKN 1 Jombang. This study used a quantitative approach with a causal method. The population in this study was all students majoring in Digital Business at SMKN 1 Jombang who had participated in the teaching factory. A sample of 210 respondents was selected using a simple random sampling technique. Data collection was conducted through an online questionnaire via Gform. The results showed that the implementation of a teaching factory, self-efficacy, and internal locus of control had a partial and simultaneous effect on student work readiness.